Scientific Opinion of Flavouring Group Evaluation 411 (FGE.411): 2‐(4‐methylphenoxy)‐N‐(1H‐pyrazol‐3‐yl)‐N‐(thiophen‐2‐ylmethyl)acetamide from chemical group 30 (miscellaneous substances) - EFSA Panel on Food Additives and Flavourings (FAF); Maged Younes; Gabriele Aquilina; Laurence Castle; Karl‐Heinz Engel; Paul Fowler; Maria Jose Frutos Fernandez; Peter Fürst; Ursula Gundert‐Remy; Rainer Gürtler; Trine Husøy; Peter Moldeus; et al. (EFSA Journal, 2018)
Abstract EFSA was requested to deliver a scientific opinion on the implications for human health of the flavouring substance 2‐(4‐methylphenoxy)‐N‐(1H‐pyrazol‐3‐yl)‐N‐(thiophen‐2‐ylmethyl)acetamide [FL‐no: 16.133], in the Flavouring Group Evaluation 411 (FGE.411), according to Regulation (EC) No 1331/2008 of the European Parliament and of the Council. The substance has not been reported to occur in natural source materials of botanical or animal origin. It is intended to be used as a flavouring substance in specific categories of food but not intended to be used in beverages, except for milk and dairy based beverages that are opaque. The chronic dietary exposure to the substance estimated using the added portions exposure technique (APET), is calculated to be 225 μg/person per day for a 60‐kg adult and 142 μg/person per day for a 15‐kg 3‐year‐old child. A 90‐day oral gavage study in rats showed no adverse effects at doses up to 100 mg/kg body weight (bw) per day, providing an adequate margin of safety. Developmental toxicity was not observed in a study with rats at the dose levels up to 1,000 mg/kg bw per day. The Panel concluded that there is no safety concern for [FL‐no: 16.133], when used as a flavouring substance at the estimated level of dietary exposure calculated using the APET approach and based on the recommended uses and use levels as specified in Appendix  B. This conclusion does not apply for use in beverages where the substance can be subject to phototransformation.